1991
DOI: 10.1111/j.1439-0434.1991.tb01190.x
|View full text |Cite
|
Sign up to set email alerts
|

Population Tendencies of Pseudomonas cichorii and P. syringae pv. garcae in Young and Mature Coffee Leaves

Abstract: The population tendencies of Pseudomonas cichorii and P. syringae pv. garcae in young and mature coffee leaves were determined by inoculating streptomycin resistant bacterial cells from 24 h cultures into young and mature coffee leaves. The leaves were then sampled daily for 5 days and the number of bacterial cells per g of leaf tissue was determined. Pseudomonas cichorii increased in mature leaves only while P. syringae pv. garcae increased in young leaves. Symptom development was dependent on the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 5 publications
0
10
0
1
Order By: Relevance
“…Perhaps emergent leaves are not the preferential site of colonization for strain PF130A. Differences in the ability of bacteria to colonize mature versus young leaves have been noted in other systems (26).…”
Section: Discussionmentioning
confidence: 88%
“…Perhaps emergent leaves are not the preferential site of colonization for strain PF130A. Differences in the ability of bacteria to colonize mature versus young leaves have been noted in other systems (26).…”
Section: Discussionmentioning
confidence: 88%
“…Unfortunately, this correlation does not distinguish between the possibility that bacterial expression of pathogenicity is causal to abundant epiphytic growth, or that a susceptible host provides an environment that is more conducive to bacterial multiplication than that of a resistant host. Symptom expression, per se, probably does not contribute significantly to an increase in population size, at least in the laboratory, since the largest population increases after inoculation usually occur before symptoms are visible (KLEMENT et al 1964;LEBEN et al 1968a;OLIVEIRA et al 1991;STADT and SAETILER 1981;WYMAN and VAN ETIEN 1982).…”
Section: Pathogenicitymentioning
confidence: 96%
“…(2006) showed that just 0·5% of the bacterial species recorded in tropical tree canopies were common to all tree species. Furthermore, both bacterial and fungal population size on leaves has been correlated with leaf position, plant architecture and height in the canopy (Wildman and Parkinson 1979; Oliveira et al. 1991; Jacques et al.…”
Section: Sources Of Microbes Colonizing the Phyllospherementioning
confidence: 99%